2018
DOI: 10.1038/s41375-018-0082-4
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing of nodal marginal zone lymphomas identifies recurrent BRAF mutations

Abstract: Nodal marginal zone lymphoma (NMZL) is a rare small B-cell lymphoma lacking disease-defining phenotype and precise diagnostic markers. To better understand the mutational landscape of NMZL, particularly in comparison to other nodal small B-cell lymphomas, we performed whole-exome sequencing, targeted high-throughput sequencing, and array-comparative genomic hybridization on a retrospective series. Our study identified for the first time recurrent, diagnostically useful, and potentially therapeutically relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 75 publications
(99 reference statements)
4
61
1
Order By: Relevance
“…Recurrently detected copy number variants and mutations found in diffuse follicular lymphoma (dFL) compared to previously published studies of conventional follicular lymphoma (cFL) and marginal zone lymphoma (MZL). CNVs in dFL detected in the present report and previously published studies* (3,20) were grouped and compared to previously published studies of cFL (4-10) and MZL (26,29,(38)(39)(40)(41). Mutations in dFL detected in the present report and previously published studies* (20,21) were grouped and compared to mutations found in previously published studies of cFL (11)(12)(13)(14)(15)(16)(17)(18)(19) and MZL (26,(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Our Data Demonstrated New Associations Of Loss/cn-loh Of 16pmentioning
confidence: 67%
See 1 more Smart Citation
“…Recurrently detected copy number variants and mutations found in diffuse follicular lymphoma (dFL) compared to previously published studies of conventional follicular lymphoma (cFL) and marginal zone lymphoma (MZL). CNVs in dFL detected in the present report and previously published studies* (3,20) were grouped and compared to previously published studies of cFL (4-10) and MZL (26,29,(38)(39)(40)(41). Mutations in dFL detected in the present report and previously published studies* (20,21) were grouped and compared to mutations found in previously published studies of cFL (11)(12)(13)(14)(15)(16)(17)(18)(19) and MZL (26,(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Our Data Demonstrated New Associations Of Loss/cn-loh Of 16pmentioning
confidence: 67%
“…Of note, 2 cases from the Siddiqi et al study were not included, as those cases had demonstrable BCL2/IGH rearrangements. The aggregate frequencies of particular alterations found in dFL were contrasted with previously published reports for cFL (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and MZL (26,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Although the previous studies describing CNVs in cFL used a variety of techniques, most of these studies (8/13, 61%) were performed using SNP-array platforms similar to the present method indicating that the results obtained in these prior studies should be comparable to our findings.…”
Section: Crebbp and Stat6 Co-mutation And 16p13 And 1p36 Loss Represementioning
confidence: 89%
“…Targeted sequencing of 20 NMZL cases also showed recurrent mutations in TNFAIP3 (30%), and CD79B (10%) . A WES study of 25 NMZL cases confirmed recurrent mutations in KMT2D (28%), KLF2 (12%), and TNFAIP3 (12%), as well as TET2 (20%), CREBBP (20%), BRAF (16%), EZH2 (16%) and TBFRSF14 (16%) . Gene expression profiling from a test set of 15 NMZL and 61 validation cases revealed a molecular signature enriched for interleukins (IL‐2, IL‐6, IL‐10), integrins, PI3K, NF‐kB, and TGF‐β .…”
Section: Introductionmentioning
confidence: 91%
“…Using this rubric, each variant was assigned into one of four categories: likely somatic, cannot exclude somatic/possibly somatic, cannot exclude somatic/possibly germline, and likely germline. Within the "cannot exclude somatic" category, variants were grouped into the possibly germline category if the gene in question had not been reported to be mutated in either dFL 20,21 , pFL 25 , cFL 14,19 , or MZL 26 . Variants assigned to the "likely somatic" and "cannot exclude somatic/possibly somatic" categories were included for further analyses.…”
Section: Targeted Next-generation Sequencing Analysismentioning
confidence: 99%